Behavioural Assessment of Migratory Nomads towards Zoonotic Importance of Scabies/ Mange Infestation - Rashid, M.; Jeelani, Rizwan; Javaid, Moien (Indian Journal of Extension Education, 2018)
Scabies is a skin disease caused by infestation and sensitization of Sarcoptes scabiei mite. It is endemic in tropical and  subtropical regions around the world and is a public health problem. The most dominant factor in the incidence of scabies  is poverty and poor individual hygiene. The purpose of this study was to the analyze the relationship between level of  education, knowledge, attitudes and practices with the incidence of scabies in sheep, goats and their rearers. A cross  sectional study was conducted with random sampling with sample of 120 respondents. The results of this study showed  that there is a significant positive association of knowledge with attitude (p=0.910) and practices (p=0.856) with scabies  events. The study reveals that low knowledge and lack of hygienic practices increases the risk and incidence of scabies.  Therefore, it is imperative to inform and educate the vulnerable societies for the prevention of this disease which not only  affects animals, but humans too and causes huge economic losses.
Keywords: Attitude; knowledge; practices; scabies